2015
DOI: 10.1146/annurev-psych-010814-015331
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Mind Wandering: Empirically Navigating the Stream of Consciousness

Abstract: Conscious experience is fluid; it rarely remains on one topic for an extended period without deviation. Its dynamic nature is illustrated by the experience of mind wandering, in which attention switches from a current task to unrelated thoughts and feelings. Studies exploring the phenomenology of mind wandering highlight the importance of its content and relation to meta-cognition in determining its functional outcomes. Examination of the information-processing demands of the mind-wandering state suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
1,424
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,352 publications
(1,480 citation statements)
references
References 166 publications
(155 reference statements)
44
1,424
3
9
Order By: Relevance
“…In recent years, it has been shown that levels of DMN activation are linked to the frequency and depth of mind‐wandering (Christoff, Gordon, Smallwood, Smith, & Schooler, 2009; Mason et al., 2007; Scheibner et al., 2017; Smallwood & Schooler, 2015). Hereby, mind‐wandering was defined as any kind of cognition independent of the task at hand, involving processes like retrieval of autobiographic memory, future planning or evaluating and judging the present (Scheibner et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it has been shown that levels of DMN activation are linked to the frequency and depth of mind‐wandering (Christoff, Gordon, Smallwood, Smith, & Schooler, 2009; Mason et al., 2007; Scheibner et al., 2017; Smallwood & Schooler, 2015). Hereby, mind‐wandering was defined as any kind of cognition independent of the task at hand, involving processes like retrieval of autobiographic memory, future planning or evaluating and judging the present (Scheibner et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, mind‐wandering was defined as any kind of cognition independent of the task at hand, involving processes like retrieval of autobiographic memory, future planning or evaluating and judging the present (Scheibner et al., 2017). Mind‐wandering has been associated with several impairments in cognitive functioning (for a review, see Smallwood & Schooler, 2015), however, a reduction in mind‐wandering, as well as concurrent decrease in the DMN could be observed when applying meditation strategies (Berkovich‐Ohana, Harel, Hahamy, Arieli, & Malach, 2016; Scheibner et al., 2017). Furthermore, these behavioral and neural changes in the DMN were associated with an increase in performance on working memory tasks (Berkovich‐Ohana et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also have consequences for the costs and benefits of mind wandering (Smallwood & Schooler, 2015). Mind wandering during tasks requiring precise timing of the environment, such as operating a motor vehicle (Yanko & Spalek, 2014), will deleteriously impact performance.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, students can also be distracted even without alluring Mind Wandering, Lecture Learning, and Situational Interest 4 stimuli. Mind wandering, which refers to daydreaming, worrying, or other forms of off-task (or context-independent) thinking, is increasingly appreciated as a frequent and important cognitive activity that confers both costs and benefits (e.g., Immordino-Yang, Christodoulou, & Singh, 2012;Kane & McVay, 2012;Smallwood & Schooler, 2015).The present study combined experimental and individual-differences approaches to identify predictors and possible consequences of mind wandering during learning, using a realistic video lecture. Within a laboratory context, we assessed a wide range of individual differences variables (e.g., WMC, background knowledge and interest, epistemic beliefs) to test five a priori hypotheses (H1-H5) about mind wandering and learning derived from the existing literature.…”
mentioning
confidence: 99%